MEDIA EDUCATION IN DIGITAL SOCIETY: AN IBERO-AMERICAN VIEW - Marta-Lazo, Carmen; Montalvo, Jorge Abelardo Cortes (European Scientific Journal, ESJ, 2015)
The analysis of the models and paradigms of communication in all the elements of the global educational system is an edu-comunication object of study. This stems from the subject to culture and the current society, with education as the motor element of the “mediation” process. Research, approaches, and proposals in the Ibero-American environment have set relevant guidelines in the course of edu-comunication. In addition, it has given arguments and sustenance to educational innovation, particularly the ones that refers to the media, informational literacy, and the development of competences. The aim of this study is to give a closer look at the “state of the matter” of the emerging paradigms of education and communication. However, this is just like some conceptual proposals in the Ibero-American geography which combines both disciplinary fields.